Characterization of bio-nanocomposite films based on gelatin/polyvinyl alcohol blend reinforced with bacterial cellulose nanowhiskers for food packaging applications. (April 2021) - Haghighi, Hossein; Gullo, Maria; La China, Salvatore; Pfeifer, Frank; Siesler, Heinz Wilhelm; Licciardello, Fabio; Pulvirenti, Andrea
Abstract: Bacterial cellulose nanowhiskers (BCNW) were synthesized from Komagataeibacter xylinus (strain K2G30; UMCC 2756) using sulfuric acid hydrolysis and incorporated into a gelatin-polyvinyl alcohol (GL/PVA) blend film matrix. The effect of BCNW content (1–10 wt% of biopolymer) on the microstructural, mechanical, optical, and water barrier properties of bio-nanocomposites was studied. Transmission electron microscopy showed that BCNW had a needle shape morphology with an average length of 600 nm and an average width of 30 nm. The crystallinity index of BCNW was 94.7% using X-ray diffraction. Scanning electron microscopy (SEM) illustrated good miscibility between GL/PVA blend film matrix and BCNW up to 7.5 wt%. Fourier-transform infrared spectroscopy in the attenuated total reflection mode showed molecular interactions between functional groups of the GL/PVA blend film matrix and BCNW. The incorporation of BCNW up to 7.5% into the GL/PVA blend reduced the water vapor transmission rate and water vapor permeability by about 22% and 14%, respectively, while tensile strength, elongation at break, and elastic modulus increased by about 21.5%, 41% and 19%, respectively (p < 0.05). Films transparency was not affected by the addition of BCNW (p > 0.05) suggesting that the BCNW were dispersed uniformly at the nanoscale. All films were colorless (ΔE*<2) with low opacity value (<2) comparable to synthetic plastics. Overall, the characterization of functional properties revealed that GL/PVA blend film reinforced with BCNW could be used as an environmentally friendly packaging material to partially replace or reduce the use of current petroleum-based packaging materials. Graphical abstract: Image 1 Highlights: Films based on Gelatin/PVA blend reinforced with BCNW were developed. Potential interaction between Gelatin/PVA blend and BCNW was demonstrated. Films containing BCNW positively affected mechanical and water barrier properties. Films containing BCNW maintained same high transparency level of the Gelatin/PVA.